A mobile-based educational intervention on media health literacy: A quasi-experimental study - Mahsa Nazarnia; Fatemeh Zarei; Nasrin Roozbahani (Tabriz University of Medical Sciences, 2023)
Background: Health misinformation on social media is a persistent public health concern that requires the proper skill set for interpreting and evaluating accurate information. This study aimed to determine the effects of a mobile app-based educational intervention on media health literacy (MHL) development among Iranian adults. Methods: This study was a quasi-experimental design conducted in 2022 that included 100 Iranian adults aged 18 to 65 years old. The inclusion criteria for participation were ownership of an Android smartphone, no prior training in MHL, and membership in at least one virtual social media app. As the primary outcome of the study, MHL was assessed using the validated MeHLit questionnaire with two follow-up time points (immediately after program completion and 12 weeks after program completion) in addition to a pre-test. Participants were divided into an experimental group that received the mobile app-based training program and a control group that received none. Results: The repeated measures test revealed a significant effect of the group-time interaction on the mean MHL score in both the intervention and control groups. Within the intervention group, the follow-up test indicated a significant increase in mean MHL scores for post-test 1 (63.54±12.57) and post-test 2 (65.72±7.97) compared to the pre-test phase (55.14±12.04), with these increases being statistically significant (P<0.001). No significant difference was observed within the control group. Conclusion: The results of this study suggest that the mobile app-based educational intervention was effective in improving MHL among Iranian adults. These findings highlight the potential of mobile app-based interventions for promoting MHL and addressing health misinformation on social media.